Wakaf dalam Perspektif al-Qur’an dan Sunnah - Muhamad Zainul Abidin (LPPM IAIT, 2023)
Waqf is one of the pillars of Islamic philanthropy that has been practiced since the early days of Islam. The Prophet and his Companions were pioneers in this regard. He encouraged and even directly set an example for the Companions by donating some of their wealth from the fai'. In Indonesia, waqf has also become a significant source of public funding. Waqf has great potential to alleviate poverty and improve the welfare of the people in a sustainable manner, because waqf assets are long-term, not limited by time. The enormous potential of waqf encourages researchers to conduct research on the concept of waqf, by exploring it directly through two authoritative sources in Islam, namely the Qur'an and Sunnah. This research is a literature research using the method of maudhu'i interpretation (thematic interpretation study) and takhrij hadith. The maudhu'i interpretation method is used to explore information deeply and holistically from the Qur'an. While the takhrij hadith method is used to obtain valid and comprehensive information from the hadith. The results show that the law of waqf according to the majority of scholars is mandub (sunnah). This is based on the shara' arguments from the Qur'an, Sunnah, and Ijma' that indicate the recommendation to endow. Waqf was widely practiced during the time of the Prophet, both by himself and his companions. The virtues of waqf are very great as stated by the Prophet, both in the Qur'an and Sunnah. Among the virtues of waqf for people who do waqf are: (1) Glory in heaven, (2) Multiplied rewards, as well as forgiveness from Allah, and (3) Rewards that will continue to flow beyond the limits of the world.